Grain size distribution of sediment core PHE1 retrieved from the Pheneos Polje (Peloponnese, Greece) - Seguin, Joana; Avramidis, Pavlos; Haug, Annette; Kessler, Torben; Schimmelmann, Arndt; Unkel, Ingmar (In: Seguin, J et al. (2020): Geochemical and sedimentological record of sediment core PHE1 retrieved from the Pheneos Polje (Peloponnese, Greece) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.921424, 2020)
The sediment core PHE1 (37.85114° N, 22.33510° E) was retrieved from the eastern bay of the Pheneos Polje, Peloponnese Greece, in spring 2017 using a piston corer (Stitz type). The sedimentary sequence covers 390 cm (sedimentary units 1 - 9). The grain size distribution <2 mm was measured on air-dried samples (ca. 0.3 g) using a laser-particle-analyser Malvern Mastersizer 2000. The core sequence covers the largest part of the Holocene and was analysed to reconstruct ecosystem and landscape changes as well as palaeoclimatic fluctuations in southern Greece.
Keywords: Eastern Mediterranean; Geochemistry; Greece; palaeoenvironment; Peloponnese; Sedimentology